Unexpected Exposures to Multilingualism in the Late Middle Ages: A Global Perspective by Travelogue Authors: Der Niederrheinische Orientbericht, Georgius of Hungary, and Johann Schiltberger - Classen, Albrecht (International Journal of Culture and History, 2024)
Whereas previous scholars interested in multilingualism have tried to identify specific textual sources for evidence confirming that phenomenon, this article takes a different approach and examines three late medieval texts (in Latin and German) where the narrator travels around many countries in the Middle East, either enjoying the freedom to do so, or forced because he had been captured by the Ottomans and sold into slavery. Even though the authors do not reveal much at all about the linguistic situation for them personally, the textual framework clearly signals that they spent a long time in complex and difficult language conditions. Although we are not told much at all about multilingualism here, the indirect conclusions allow us to confirm the extensive presence of numerous multilingual speakers, including the three authors.